Aplikasi e-Vote Pemilihan Ketua Badan Eksekutif Mahasiswa Universitas Budi Luhur Berbasis Web - Destiansari, Desti; Destiansari Istinabiyah, Desti (Proceedings of the Informatics Conference, 2024)
The election of the Student Executive Board (BEM) president is an event for implementing regeneration or leadership transition within student organizations, particularly in the management of the Student Executive Board. In carrying out this election, several obstacles often occur, ranging from issues in using facilities for allocating election equipment to instances of human error. These problems led to the idea of conducting the student president election using web-based technology, making the process easier and more efficient, known as E-voting. The system development method used in this study is Extreme Programming, with the steps of planning, design, coding, and testing. The system design tools used include class diagrams, activity diagrams, and use case diagrams. This study resulted in a web-based E-Vote application for the BEM President Election at Universitas Budi Luhur, which is capable of making the election process more effective and efficient.